الشلل الدماغي متلازمة المعاناة والعجز - حافري سميرة (جامعة محمد بوضياف -المسيلة, 2024)
تعد صحة الاولاد اكبر هواجس الأهل في ظل انتشار سلسلة من الامراض الغامضة والمعاصرة والتي اصبح من الضروري معرفتها ومعرفة كيفية مجابهتها ومن اهمها مرض الشلل الدماغي الذي يعد في وقتنا الحالي كثير الانتشار نظرا لتفشي عدد هائل من الظواهر السلبية في مجتمعاتنا والتي تؤثر بشكل واضح على حياة الفرد والأسرة بما فيها صحه النساء الحوامل والأطفال خصوصا على اعتبار ان هاتين الفئتين تعنيان بشكل مباشر بهذا المرض حيث حاولنا في هذا الريبورتاج الإجابة على مجموعه أهمها ما هو الشلل الدماغي ما هي اعراضه واسبابه وما هي اكبر اثاره على حياة الفرد والأسرة . الكلمات المفتاحية: الشلل الدماغي، الشلل الرباعي، الفرد، الأسرة Summary Children's health is the biggest concern of parents in light of the spread of a series of mysterious and contemporary diseases that have become necessary to know and how to confront them, the most important of which is cerebral palsy, which is currently widespread due to the spread of a huge number of negative phenomena in our societies that clearly affect the life of the individual. And the family, including the health of pregnant women and children, especially considering that these two groups are directly concerned with this disease. In this report, we have tried to answer a number of questions, the most important of which is what is cerebral palsy, what are its symptoms and causes, and what are its greatest effects on the life of the individual and the family. Keywords: cerebral palsy, quadriplegia, individual, family